Structural Basis for the High-Affinity Inhibition of Mammalian Membranous Adenylyl Cyclase by 2′,3′-O-(N-Methylanthraniloyl)-Inosine 5′-Triphosphate - Hübner, Melanie (The American Society for Pharmacology and Experimental Therapeutics, 2011)
2′,3′-O-(N-Methylanthraniloyl)-ITP (MANT-ITP) is the most potent inhibitor of mammalian membranous adenylyl cyclase (mAC) 5 (AC5, K(i), 1 nM) yet discovered and surpasses the potency of MANT-GTP by 55-fold (J Pharmacol Exp Ther 329:1156–1165, 2009). AC5 inhibitors may be valuable drugs for treatment of heart failure. The aim of this study was to elucidate the structural basis for the high-affinity inhibition of mAC by MANT-ITP. MANT-ITP was a considerably more potent inhibitor of the purified catalytic domains VC1 and IIC2 of mAC than MANT-GTP (K(i), 0.7 versus 18 nM). Moreover, there was considerably more efficient fluorescence resonance energy transfer between Trp1020 of IIC2 and the MANT group of MANT-ITP compared with MANT-GTP, indicating optimal interaction of the MANT group of MANT-ITP with the hydrophobic pocket. The crystal structure of MANT-ITP in complex with the G(s)α- and forskolin-activated catalytic domains VC1:IIC2 compared with the existing MANT-GTP crystal structure revealed only subtle differences in binding mode. The higher affinity of MANT-ITP to mAC compared with MANT-GTP is probably due to fewer stereochemical constraints upon the nucleotide base in the purine binding pocket, allowing a stronger interaction with the hydrophobic regions of IIC2 domain, as assessed by fluorescence spectroscopy. Stronger interaction is also achieved in the phosphate-binding site. The triphosphate group of MANT-ITP exhibits better metal coordination than the triphosphate group of MANT-GTP, as confirmed by molecular dynamics simulations. Collectively, the subtle differences in ligand structure have profound effects on affinity for mAC.